Fatigue life equality of polished and electrical discharge machined WC-Co hard metal achieved solely by wet blasting. (September 2016) - Klünsner, T.; Morstein, M.; Marsoner, S.; Deller, M.; Marklein, B.
Abstract: WC-Co hard metals are materials widely used in wear applications, metal machining and highly fatigue loaded tools. Shaping tools and components made of hard metals often requires electrical discharge machining (EDM) that is well-known to negatively influence the material's fatigue properties. The current work demonstrates that it is possible to achieve a fatigue limit of electrical discharge machined specimens equal to the one of finely ground and polished reference samples. This is achieved by the application of advanced wire EDM technology combined with a sole surface post-treatment step of abrasive blasting. Stress amplitude-life curves were determined in a four point bending test setup. Depth profiles of residual stress were determined by means of X-ray diffraction for electrical discharge machined samples prior to and after blasting. Surface defect size was documented in metallographic cross sections by scanning electron microscopy. The surface residual stress state was found to be crucially important regarding the observed fatigue behavior. If the applied EMD technology produces cracks shallow enough to allow for their removal by abrasive blasting and compressive residual stress is introduced as deep into the surface as damage reaches, the negative effect of EDM on the fatigue limit is neutralized. Highlights: Fatigue behavior of polished and EDM cut & blasted WC-Co hard metal are equal. Surface defect depth minimized to WC grain size by advanced EDM technology. After blasting compressive residual stress acts as deep as surface defects are present. After blasting the surface exhibits compressive residual stress in the WC and Co phases.